Genetic variability and divergence studies in sesame (Sesamum indicum L.): GENETIC VARIABILITY AND DIVERGENCE STUDIES IN SESAME - BABITA KUMARI; S R KUMHAR (Journal of Oilseeds Research, 2019)
Genetic variability and divergence were studied in 40 genotypes/varieties of sesame for eleven yield and yield related traits. Analysis of variance exhibited significant differences for all the characters suggesting the presence of large amount of inherent genetic variability among the genotypes studied. The maximum magnitudes of phenotypic coefficient of variance (PCV) and genotypic coefficient of variance (GCV) were observed for number of primary branches per plant, number of capsules per plant and capsule bearing length (cm). Estimates of heritability was high for number of primary branches per plant, days to 50% flowering and seed yield, days to maturity, and high heritability coupled with high genetic advance as 5% of mean was observed for number of primary branches per plant and seed yield per plant suggesting additive gene action for expression of these characters. The hierarchical cluster analysis indicated the presence of considerable genetic divergence among the genotypes/varieties. The genotypes were grouped into seven clusters using Ward’s minimum variance method. The inter-cluster Euclidean2 distance was maximum between cluster-III and VII (68.33) followed by cluster-IV and VII (61.40) and cluster-II and VII (59.59) which indicated that the genotypes included in these clusters could give high heterotic response and thus better segregants. The maximum cluster means were revealed by cluster-II for number of capsules per plant, capsule bearing length and seed yield per plant followed by cluster VII for number of primary branches per plant and 1000 seed weight, and cluster-VI for number of seeds per capsule. Based on this observation, it could be concluded that genotypes carefully chosen from clusters II, VI and VII, would offer a better scope of improvement of sesame through recombination breeding.